The water striders of Pakistan (Hemiptera: Heteroptera: Gerridae): new records from Punjab and first checklist for the country - Cianferoni, Fabio; Saleem, Rukhshanda; Afsheen, Sumera; Zia, Ahmed (Zootaxa, 2021)
This study was conducted to explore the gerrid fauna of the Industrial Triangle of Punjab (Pakistan). Five species were collected during this study, of which three are recorded for the first time for Pakistan: Metrocoris communis (Distant, 1910), Heterobates bilobatus (Esaki, 1927), and Naboandelus bergevini popovi Brown, 1951. A sixth species was added from Punjab (Pakistan) from museum material, and two others from Indian Kashmir. For two taxa, H. bilobatus and N. bergevini popovi, the new records extended their known range. Further, Rheumatobates maculata Khatoon & Ali, 1978 is proposed as a junior synonym of Metrocoris communis (Distant, 1910) and Gerris lacustris (Linnaeus, 1758) is excluded from the Pakistani fauna. The first provisional checklist for the Gerridae of Pakistan is presented and the gerrid fauna of neighboring countries to Pakistan is discussed.